Induction of ganglioside synthesis in Drosophila brain accelerates assembly of amyloid ? protein. - Yamasaki, Y.; Tsuda, L.; Suzuki, A.; Yanagisawa, K. (Scientific reports, 2018)
The assembly and deposition of amyloid ? protein (A?) is a fundamental event during the early stages of Alzheimer's disease (AD) and cerebral amyloid angiopathy. A growing body of evidence indicates that gangliosides form a pathological platform for the generation of ganglioside-bound A?, which facilitates the assembly of soluble A?s; however, the molecular mechanisms underlying the binding of A? to gangliosides in the brain remain unclear due to the lack of an in vivo system that may address this issue. In insects, including the fruit fly Drosophila melanogaster, gangliosides are not intrinsically present at a detectable level. We herein demonstrate that ganglioside expression is inducible in Drosophila via the expression of transgenes of ganglioside synthesis enzymes and the feeding of exogenous sialic acid, and also that the induction of ganglioside synthesis significantly accelerates A? assembly in vivo. Our results support the hypothesis that gangliosides are responsible for A? assembly in vivo and also provide an opportunity to develop a valuable model for basic research as well as a therapeutic strategy for AD.